1996
DOI: 10.1016/s0370-2693(96)01167-7
|View full text |Cite
|
Sign up to set email alerts
|

Topological defects in gauge theories of open p-branes

Abstract: We study phase transitions induced by topological defects in compact Abelian gauge theories of open p-branes in (d+1) space-time dimensions. Starting from a massive antisymmetric tensor theory for the open p-branes we show how the condensation of topological defects can lead to a decoupled phase with a massless tensor coupled to closed (p − 1)-branes and a massive tensor coupled to open (p + 1)-branes. We also consider the case, relevant in string theory, in which the boundaries of the p-branes are constrained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In [10] it was proved that the confinement phase we found in the 4-dimensional case and for rank p = 1 for the MGTs described by the action (2.3), is present also in arbitrary space-time dimensions and for arbitrary p (p ≤ d − 1). Simply invoquing the duality we know that the phase is present also in the TMGTs, described by the action (2.4), in arbitrary space-time dimensions and for arbitrary rank antysymmetric tensor fields.…”
Section: Condensation Of Topological Defects In the 4-dimensional Casementioning
confidence: 77%
See 1 more Smart Citation
“…In [10] it was proved that the confinement phase we found in the 4-dimensional case and for rank p = 1 for the MGTs described by the action (2.3), is present also in arbitrary space-time dimensions and for arbitrary p (p ≤ d − 1). Simply invoquing the duality we know that the phase is present also in the TMGTs, described by the action (2.4), in arbitrary space-time dimensions and for arbitrary rank antysymmetric tensor fields.…”
Section: Condensation Of Topological Defects In the 4-dimensional Casementioning
confidence: 77%
“…In this magnetic condensation phase, a lenghty calculation shows that the self energy of a circular charge loop of radius R is proportional to R ln R, and this gives rise to logarithmic confinement of electric strings (logarithmic confinement phase) [18]. The monopoles Q are always in a plasma phase : their condensation (after the condensation of t µ ), as it was shown in [10], gives a volume law and thus the usual confinement strings.…”
Section: Condensation Of Topological Defects In the 4-dimensional Casementioning
confidence: 87%
“…In recent years, the study of p-branes are also of importance in understanding string duality, M-theory unification and small distance structure of space (space-time). As they have also been proved to be topological defects in gauge theory [6][7][8], we can study them by using some proper topological methods. The starting point of this paper is to find a gauge field theory foundation of the φ-mapping topological current of p-branes introduced in our previous work [9].…”
Section: Introductionmentioning
confidence: 99%
“…In resent years, CS p-branes have also been proven to be topological defects in gauge theory [13][14][15]. Antisymmetric tensor gauge fields determine all of the features of a p-brane and have been widely studied in the theory of p-brane [14,[16][17][18][19][20].…”
mentioning
confidence: 99%
“…Antisymmetric tensor gauge fields determine all of the features of a p-brane and have been widely studied in the theory of p-brane [14,[16][17][18][19][20]. For example, in [14,[20][21][22][23][24], from the perspective of a higher dimensional theory, the topological theories of p-branes in M-theory were studied. Ren et al [6] found that the topological p-branes are created at every isolated zero of order parameter field φ.…”
mentioning
confidence: 99%